Klossowski, l'incommunicable - Waelti, Slaven (Histoire des Idées et Critique Littéraire, 2015)
Can we communicate the incommunicable? Language is general, but the "depths of the soul" are unique, and only the experience lived in silence is authentic. Would it be possible to find a language that would appear to say something but that would communicate nothing but the incommunicable? The present volume analyses how, by developing the simulacrum of a language or "pure media", Klossowski managed to move beyond the prevarications of Gide, so hesitant to speak or remain silent about his "Uranianism", and the wrath of Bataille or Sade, equating destruction and purity, to finally arrive at the Nietzschean innocence that creates gods.